2019
DOI: 10.1111/gcbb.12628
|View full text |Cite
|
Sign up to set email alerts
|

Soil & Water Assessment Tool (SWAT) simulated hydrological impacts of land use change from temperate grassland to energy crops: A case study in western UK

Abstract: When considering the large‐scale deployment of bioenergy crops, it is important to understand the implication for ecosystem hydrological processes and the influences of crop type and location. Based on the potential for future land use change (LUC), the 10,280 km2 West Wales Water Framework Directive River Basin District (UK) was selected as a typical grassland dominated district, and the Soil & Water Assessment Tool (SWAT) hydrology model with a geographic information systems interface was used to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…These parameters represent hydrology and water quality (Tables A1 and A2, respectively) while being indirectly related to vegetation dynamics. Although SWAT is relatively well equipped with many biophysical parameters and process conceptualizations that directly influence vegetation dynamics (e.g., maximum root depth, radiation use efficiency, stomatal conductance, day/nighttime thresholds of vapor pressure deficit) [7,55], other advanced watershed models are not [23,24,56]. Therefore, we excluded such parameters from our calibration [unlike previous studies, (e.g., [8,13]) to isolate the effects of MODIS LAI assimilation into the model and to maintain focus on our study's hypothesis that assimilated LAI data can serve as a proxy for vegetation dynamics when limited (or completely absent) vegetation-related parameters and processes are available in watershed models.…”
Section: Model Calibrationmentioning
confidence: 99%
“…These parameters represent hydrology and water quality (Tables A1 and A2, respectively) while being indirectly related to vegetation dynamics. Although SWAT is relatively well equipped with many biophysical parameters and process conceptualizations that directly influence vegetation dynamics (e.g., maximum root depth, radiation use efficiency, stomatal conductance, day/nighttime thresholds of vapor pressure deficit) [7,55], other advanced watershed models are not [23,24,56]. Therefore, we excluded such parameters from our calibration [unlike previous studies, (e.g., [8,13]) to isolate the effects of MODIS LAI assimilation into the model and to maintain focus on our study's hypothesis that assimilated LAI data can serve as a proxy for vegetation dynamics when limited (or completely absent) vegetation-related parameters and processes are available in watershed models.…”
Section: Model Calibrationmentioning
confidence: 99%
“…Here, we included relevant biophysical parameters during the streamflow calibration process using the aggregated (or lumped) approach (Chen et al, 2017; Cibin et al, 2016; Demissie et al, 2017; Holder et al, 2019). Recent research in watershed modeling has shown improvements in hydrology and water quality predictions with the assimilation of remotely sensed biophysical data (e.g., LAI; Ma et al, 2019; Rajib et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrologic models are ideal tools for predicting the hydrologic responses and nutrient and sediment loads for future scenarios at watershed scales. Soil and Water Assessment Tool (SWAT; Arnold et al, 2012) is one of the most broadly applied watershed models that has been used for evaluating the effects of biofuel‐related scenarios on hydrology and water quality (Chen et al, 2017; Cibin et al, 2016; Engel et al, 2010; Holder et al, 2019). However, many bioenergy crops such as carinata are not represented in the SWAT plant database and other watershed models.…”
Section: Introductionmentioning
confidence: 99%
“…The water‐use efficiency (WUE) of miscanthus, due to its C 4 photosynthesis and grass leaf morphology, is much higher than most arable crops grown in Europe, with WUEs ranging from 11 to 14 g dry above‐ground biomass, per liter of water transpired, compared to 1–5 g L −1 typical for barley, wheat, and maize (Clifton‐Brown & Lewandowski, 2000; Mueller et al., 2005). However, to achieve higher biomass yields, miscanthus has a high‐water demand which can affect the hydrological balance of soils (Clifton‐Brown et al., 2002; Holder, Rowe, et al., 2019). When not irrigated, summer droughts have caused yield reductions of up to 40%–45% (Richter et al., 2008; Van der Weijde et al., 2017; Awty‐Carrol et al., unpublished).…”
Section: What Are the Main Ecosystem Service Impacts To Be Considered...mentioning
confidence: 99%
“…For example, characteristics of large leaf area index, high level of rainfall interception, improved soil water infiltration, and greater capacity to extract soil water (ET) make certain miscanthus genotypes, like M. x giganteus very useful crops for land prone to waterlogging and inclusion as part of flood mitigation strategies (Holder et al., 2018; Holder, Rowe, et al., 2019). The dense, stiff‐stemmed nature of mature miscanthus grass has been shown to provide a natural barrier, reducing particulates and run‐off flow rates, and providing resistance to overland flows which make it useful as a flood defense measure by creating a leaky barrier (Holder, Rowe, et al., 2019; Shepherd, Clifton‐Brown, et al., 2020). It has also been shown to survive flooding with little impact on yield under glasshouse and winter field conditions (De Vega et al., 2021; Kam et al., 2020).…”
Section: What Are the Main Ecosystem Service Impacts To Be Considered...mentioning
confidence: 99%